Keberhasilan Usaha UKM Sektor Ritel Fashion: Kebahagiaan Pelanggan, Ketersediaan Barang dan Desain Interior Outlet - Junedi, Junedi; Gopar, Ida Abdul; Handayani, Langgeng Sri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research aims to analyze the influence of customer happiness, availability of goods and outlet interior design on business success. In an era of increasingly tight business competition, entrepreneurs are faced with the challenge of maintaining customer satisfaction while improving business performance. This research uses quantitative methods with a survey approach, involving one hundred SME entrepreneurs in the Fashion Retail Sector operating in the Bekasi District area. Analysis was carried out through validity and reliability tests, classical assumption testing and regression analysis to measure the relationship between the collected data variables. The research results show that there is a significant influence: 1). Customer Happiness (KP), 2). Availability of Goods (KB) and 3). Outlet Interior Design (DIO) on Business Success (KU) with the regression equation KU=1.044+0.650KP+0.306KB+0.137DIO. The research results show that customer happiness, availability of goods, and outlet interior design have a significant influence on the success of fashion retail SME businesses. The implications of this research highlight the importance of a holistic strategy in managing customer relationships, maintaining goods availability and designing attractive outlet interiors to increase the competitiveness of fashion retail SMEs.